Roblox addiction and psychological well-being in Generation Z - Adithya, Alfian Ricko; Hastuti, Rahmah (INSPIRA: Indonesian Journal of Psychological Research, 2025)
This study aimed to investigate the relationship between Roblox online game addiction tendency and psychological well-being among Generation Z in Greater Jakarta (Jabodetabek). The research was motivated by the increasing use of the online game Roblox, which has the potential to foster addictive behaviors and diminish psychological well-being. Using a correlational quantitative method, non-parametric Spearman's Rank and Kruskal-Wallis analyses were employed due to non-normally distributed data. Participants consisted of 273 Generation Z individuals selected via purposive sampling. The results indicated a significant negative correlation between Roblox addiction and psychological well-being (r = -.752, p < .01), suggesting that higher addiction levels are associated with lower psychological well-being. The conflict dimension contributed most substantially to the decline in psychological well-being. Furthermore, significant differences were found based on age, residence, frequency of play, duration of play, and reasons for playing. Theoretically, these findings contribute to the literature on the relationship between Roblox addiction and the psychological well-being of Generation Z, while also highlighting opportunities for future research on potential mediating or moderating variables such as self-control and social support. Practically, the results are expected to serve as an educational foundation for adolescents, parents, and educational institutions to promote self-regulation in playing Roblox.